Individual Approach to Prescribing Sodium-Glucose Co-Transporter 2 Inhibitors in Patients with Hypertrophic Cardiomyopathy - Vira Y. Tseluyko; Olena O. Butko; Kostiantyn Yu. Kinoshenko; Viktoriia V. Biletska (Ukrainian Journal of Cardiovascular Surgery, 2024)
Hypertrophic cardiomyopathy (HCM) is a common hereditary disease of the myocardium. Sodium-glucose co-transporter 2 inhibitors are recognized as first-line drugs for the treatment of heart failure, but at the moment there is little known about their use in HCM.The aim. To assess the possibility of using an acute test with empagliflozin in patients with HCM with echocardiographic assessment of left ventricular outflow tract (LVOT) obstruction.Materials and methods. Twenty-six non-obstructive HCM patients were examined. All the patients underwent an acute test with sodium-glucose co-transporter 2 inhibitor using 10 mg of empagliflozin and echocardiographic examination before and 3 hours after administration. Twenty-four patients were included in the further analysis (2 patients were excluded due to arrhythmia). The patients were divided into two groups: group 1 included subjects with an increase in LVOT pressure after empagliflozin (12 patients), group 2 included those without an increase in the gradient (12 patients).Results. During the acute test, an increase in LVOT gradient occurred in 12 patients, and in 6 patients the gradient increased significantly and reached more than 30 mm Hg. The indicator at rest in patients before the test was 11.2 (10.1-19), after the test it was 12.45 (8.9-17) mm Hg (p = 0.042). The indicator at the height of the Valsalva test also increased from 15 (11-29) to 15.45 (10.4-33) mm Hg (p=0.29). Comparative analysis of clinical and echocardiographic data did not show significant difference between the groups.Conclusions. In some patients with HCM without signs of overt or latent obstruction at the baseline, a significant increase in LVOT pressure was noted after acute test with empagliflozin. Conducting an acute test in patients with HCM is appropriate to determine the possibility of the development of LVOT obstruction while taking the drug.